Development of 3D spatial profiles to support the full lifecycle of 3D objects. (November 2020) - Kalogianni, Eftychia; Dimopoulou, Efi; Thompson, Rodney James; Lemmen, Christiaan; Ying, Shen; van Oosterom, Peter
Highlights: Development of 3D spatial profiles. Land administration in the context of spatial development lifecycle of 3D objects. Main issues of the ISO 1952 LADM revision.